2014
DOI: 10.1021/ar500280m
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Raman Spectroscopy in Graphene and MoS2-type Transition Metal Dichalcogenides

Abstract: CONSPECTUS: Raman spectroscopy is one of the most powerful experimental tools to study graphene, since it provides much useful information for sample characterization. In this Account, we show that this technique is also convenient to study other bidimensional materials beyond graphene, and we will focus on the semiconducting transition metal dichalcogenides (MX2), specifically on MoS2 and WS2. We start by comparing the atomic structure of graphene and 2H-MX2 as a function of the number of layers in the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(174 citation statements)
references
References 43 publications
7
164
1
2
Order By: Relevance
“…A group-theoretical analysis of the optical lattice vibrations for the bulk [1] reveals four Raman-active modes corresponding to the following symmetries with measured frequencies under ambient conditions: E -1 ). In addition to observation of first-order Raman lines these and other studies showed a rich multiphonon spectrum [2,3,6,7,9,10,[13][14][15] with sensitivity to excitation energy [6,7,9,10,13].…”
Section: Introductionmentioning
confidence: 74%
“…A group-theoretical analysis of the optical lattice vibrations for the bulk [1] reveals four Raman-active modes corresponding to the following symmetries with measured frequencies under ambient conditions: E -1 ). In addition to observation of first-order Raman lines these and other studies showed a rich multiphonon spectrum [2,3,6,7,9,10,[13][14][15] with sensitivity to excitation energy [6,7,9,10,13].…”
Section: Introductionmentioning
confidence: 74%
“…The explanation for this preferential phonon activation within the Brillouin zone might be similar to the one suggested for the origin of the 2LA(M) band. Indeed, it has been recently shown that this band becomes more intense than the first-order A 1 and E peaks when the Raman experiment is performed with laser energies around 2 eV, which corresponds to the B-exciton energy in 1L-MoS 2 [42]. The mechanism proposed to account for this behavior is a double resonance (DR) process which involves two LA(M) phonons with opposite momentum.…”
Section: Resultsmentioning
confidence: 99%
“…SC-TMDs hold a finite band-gap and therefore resonant Raman spectroscopy is only possible if the incoming or scattered light meets a fundamental optically active interband transition [134,136] . In this respect, resonant Raman spectroscopy with varying photon energies provides a complementary tool to emission and absorption measurements to access the electronic structure in SCTMDs as well as to study fundamental aspects of the electron-phonon interaction [134,136,137] . Already nonresonant Raman spectroscopy, meaning that neither the exciting (incoming resonance) nor the scattered photon energy (outgoing resonance) meet an optically active interband transition of the electronic bands, provides access to the number of layers [81,[138][139][140][141][142] , phase transition 2H, 3R, 1T, 1T' MX2 crystals [137,143,144] , strain [69,145,146] , disorder and defects [147] , doping [74,148] and temperature as well as thermal conductivity [97,[149][150][151][152] .…”
Section: First Order Phonon Modes As Unique Fingerprint For Materials mentioning
confidence: 99%